2014
DOI: 10.1115/1.4026256
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Loading Influence the Predicted Bone Remodeling Around Cemented Hip Replacements

Abstract: Periprosthetic bone remodeling is frequently observed after total hip replacement. Reduced bone density increases the implant and bone fracture risk, and a gross loss of bone density challenges fixation in subsequent revision surgery. Computational approaches allow bone remodeling to be predicted in agreement with the general clinical observations of proximal resorption and distal hypertrophy. However, these models do not reproduce other clinically observed bone density trends, including faster stabilizing mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 53 publications
(80 reference statements)
2
8
0
Order By: Relevance
“…Clinical DXA scanning in Furlong and Charnley stems in patients with one of each prosthesis (Chandran et al 2012) demonstrated higher BMD in all Gruen Zones except for 4, reaching significant levels in GZs 2,3,5 and 6. This is consistent with the trends predicted by the models in the present and preceding study (Dickinson 2014) (Table 2, Figure 7), in particular proximally, and the focus of distal hypertrophy predicted by the present Furlong model study can be attributed to the relatively large size implant selected for the selected bone, which fills the canal and thus leaves little space for trabecular densification in GZs 3 and 5.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Clinical DXA scanning in Furlong and Charnley stems in patients with one of each prosthesis (Chandran et al 2012) demonstrated higher BMD in all Gruen Zones except for 4, reaching significant levels in GZs 2,3,5 and 6. This is consistent with the trends predicted by the models in the present and preceding study (Dickinson 2014) (Table 2, Figure 7), in particular proximally, and the focus of distal hypertrophy predicted by the present Furlong model study can be attributed to the relatively large size implant selected for the selected bone, which fills the canal and thus leaves little space for trabecular densification in GZs 3 and 5.…”
Section: Discussionsupporting
confidence: 92%
“…In the THR model, bone remodelling alone was considered. In the RHR model, a combined periprosthetic defect healing -bone remodelling process was used (Dickinson et al 2012), which accounted for the diffusion of mesenchymal stem cells into the surgical defect created to accommodate the implant metaphyseal stem, and their subsequent differentiation and maturation in response to mechanobiological stimuli (Claes and Heigele 1999 Time-varying activity and loading factors (Fact and Fload) were applied to the remodelling stimuli to account for the described effects of walking aid use preoperatively and during rehabilitation, and gradual recovery from surgery to a higher level activity than the symptomatic preoperative reference case (Dickinson 2014). These scaling factors were applied directly to the remodelling stimulus signal, rather than to the FE model loading; the validity of this method holds while the FE model maintains approximately linear load-strain behaviour.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Gruen zones 4 and 5 exhibited maximum mineral recovery (~1 -5%) after 4 post-operative years. The early drop in BMD in the short postoperative term is likely to be related to surgically introduced microdamage and reduced immediate postoperative activity and joint loading, 39 and the osteoclastic remodelling transient which occurs prior to osteoblastic bone densification, which is measurable following THA. 40 In an extended follow-up study (mean duration of follow-up 22.5 years) with hydroxyapatite-coated (HAC) Furlong stems, Sandiford et al 41 reported localized bone resorption immediately under the collar (Gruen zone 7).…”
Section: Discussionmentioning
confidence: 99%